The Exception Rights Utilization Strategy to Enhance Defendant's Freedom Protection in Criminal Justice Proceedings - Sulistyowati, Sulistyowati; Maharani, Dewi Nadya (International Journal of Law Reconstruction, 2024)
The criminal justice must be carried out based on the Code of Criminal Procedure. According to Article 156, paragraph (1), the exception is the right of the defendant to answer the indictment given by the Public Prosecutor. The memorandum of objection must be made well when observing the indictment. If there are weaknesses in the indictment, they must be disclosed in the exception appropriately so that the results are optimal in restoring the defendant's human rights that had been deprived, in the form of freedom if the defendant is detained. The case does not proceed as in the Interim Decision number 1473/Pid.Sus/2017/PN Jkt.Sel. When it wants to continue as a case, the prosecutor must make a new indictment. The goal is to optimize so that the rights of the accused remain protected. That then there are efforts of the public prosecutor is a natural thing. The research method in this study is juridical normative. Data collection by making court decisions is also done through literature research.